A ternary complex model of Sirtuin4-NAD+-Glutamate dehydrogenase. (June 2018) - Kato, Yusuke; Kihara, Hiroshi; Fukui, Kiyoshi; Kojima, Masaki
Graphical abstract: Highlights: Homology models of Sitruin4 were built and evaluated. A Sirtuin4 model complexed with NAD + and glutamate dehydrogenase was built. Acetylated Lys171 of glutamate dehydrogenase and NAD + were close to each other. These suggest the mechanism of ADP-ribosylation of glutamate dehydrogenase. Abstract: Sirtuin4 (Sirt4) is one of the mammalian homologues of Silent information regulator 2 (Sir2), which promotes the longevity of yeast, C. elegans, fruit flies and mice. Sirt4 is localized in the mitochondria, where it contributes to preventing the development of cancers and ischemic heart disease through regulating energy metabolism. The ADP-ribosylation of glutamate dehydrogenase (GDH), which is catalyzed by Sirt4, downregulates the TCA cycle. However, this reaction mechanism is obscure, because the structure of Sirt4 is unknown. We here constructed structural models of Sirt4 by homology modeling and threading, and docked nicotinamide adenine dinucleotide + (NAD + ) to Sirt4. In addition, a partial GDH structure was docked to the Sirt4-NAD + complex model. In the ternary complex model of Sirt4-NAD + -GDH, the acetylated lysine 171 of GDH is located close to NAD + . This suggests a possible mechanism underlying the ADP-ribosylation at cysteine 172, which may occur through a transient intermediate with ADP-ribosylation at the acetylated lysine 171. These results may be useful in designing drugs for the treatment of cancers and ischemic heart disease.